Coping with friction during technology commercialisation. Issue 2 (12th June 2017) - Mattila, Malla
Abstract : Purpose: The purpose of this paper is to move forward the understanding of sociomaterial and processual aspects of innovation by describing and analysing actors' disalignment processes regarding what resources to provide and strategies for resolution of disalignments during technology commercialisation. Design/methodology/approach: The study is based on a longitudinal qualitative empirical case study depicting the commercialisation journey of a radical invention, intelligent paper, between the years of 1997 and 2009. The invention concerns cost-effective, high-volume and roll-to-roll production of printable optics and electronics enabling novel, intelligent functionalities on printed matter. Findings: The study identifies three technology commercialisation phases which involve both destructive and constructive situations of disalignment, namely, actors' multiplexity, punctualised actor roles and "not-programmatic" behaviours. Several strategies are utilised to resolve these, including seduction, pressuring, the introduction of new critical actors, organisational restructurings, selective silencing, career development opportunities, and joint technology development and commercialisation work. Research limitations/implications: The chosen methodology excludes investigating actors' micro-processes during technology commercialisation and the generalisability of the findings. Originality/value: The study develops the understanding of the changing, multiplex and negotiated actors' roles as well as their disalignment regarding what resources to provide during technology commercialisation. It complements perspectives of friction in innovation making and challenges the established industrial marketing and purchasing research of stable industrial networks by presenting a case in which a radical invention results in a new business network.